Does Sin Still Come to Christians? The Perspective of 1 John 3:9 - Sapalakkai, Rini Sumanti (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
Sin has been a major problem since the fall of man. This is the reason for Jesus' reincarnation into the world: to redeem humankind from sin. However, even though the cross has taken place, the discussion about sin continues, especially in search of an answer as to whether Christians still sin even after being redeemed by the blood of Jesus. This article answers that question through the exegesis of one of the verses in New Testament studies, namely First John 3:9. An exploration of the meaning will be done on the statement that everyone born of God does not sin anymore. The research concludes that first, sin must be purified or sanctified through Jesus, the true redeemer. Second, Christians must decide to confess each of their sins and show repentance as a sign that Jesus has redeemed them. Thirdly, the Christian must build a new lifestyle by ceasing sin. In this case, despite being redeemed, the process and goal for Christians are still happening, and the process must be won as a characteristic of true Christianity.